An Evaluation of Factors Related to the Implementation Code Blue System in the Inpatient Room of Hospital Medical Partner Bandar Klippa - Arna Fransisca Mp; Chrismis Novalinda Ginting; Sri Wahyuni Nasution; Ali Napiah Nasution (Budapest International Research and Critics University, 2022)
Implementation of the Code Blue System in the Hospital Inpatient Room. Mitra Medika Bandar Klippa is still being found. Constraints that occur are related to human resources (HR), facilities, response time, and Standard Operating Procedures (SPO). This study aims to determine the factors related to the implementation of the Code Blue System in the Hospital Inpatient Room. Mitra Medika Bandar Klippa. The type of research used is descriptive qualitative research with a phenomenological approach. The population in this study was the entire Code Blue team in the Hospital Inpatient Room. Mitra Medika Bandar Klippa and a sample of 9 people. Collecting data with primary and secondary data and analyzed by three interrelated sub-processes, namely data reduction, data display, and conclusion drawing/verification. The results showed that Human Resources (HR), facilities, response time, and Standard Operating Procedures (SPO) were related to the implementation of the Code Blue System at Mitra Medika Hospital Bandar Klippa. The response time factor that is not always on time is due to the distance of the room being too far and the busyness in the ER/ICU at the same time as the code blue activation incident.